Предмет: Математика,
автор: oks1999
решите уравнение: log3 (2^-x - 3) + log3(2^-x - 1)= 1
Ответы
Автор ответа:
0
log₃(2⁻ˣ - 3) + log₃(2⁻ˣ - 1)= 1
Пусть 2⁻ˣ =у,тогда получаем log₃(у - 3) + log₃(у - 1)= 1 или
log₃((у - 3)·(у - 1))= log₃3.Тогда верно:
(у - 3)·(у - 1)=3 или у²-4у+3=3 ,у-4у=0, у(у-4)=0 и
у₁=0 и у₂=4.
Т.к. 2⁻ˣ >0 ,то у₁=0 не подходит и мы получаем:
2⁻ˣ=4, 2⁻ˣ=2²,-х=2,х=-2-ответ
Пусть 2⁻ˣ =у,тогда получаем log₃(у - 3) + log₃(у - 1)= 1 или
log₃((у - 3)·(у - 1))= log₃3.Тогда верно:
(у - 3)·(у - 1)=3 или у²-4у+3=3 ,у-4у=0, у(у-4)=0 и
у₁=0 и у₂=4.
Т.к. 2⁻ˣ >0 ,то у₁=0 не подходит и мы получаем:
2⁻ˣ=4, 2⁻ˣ=2²,-х=2,х=-2-ответ
Похожие вопросы
Предмет: Русский язык,
автор: ajar2003donen
Предмет: Математика,
автор: mmaxmoroz
Предмет: Математика,
автор: Аноним
Предмет: Математика,
автор: nataliustinka